Rubella Hemagglutination Inhibition: Removal of Nonspecific Agglutination Due to Manganous Chloride - Biano, S. A. (1974)
Nonspecific inhibitors of rubella hemagglutination can be removed by treatment of sera with heparin-manganous chloride for use in the hemagglutination-inhibition test. After removal of nonspecific inhibitors by this procedure, an excess of manganous chloride may remain. This may cause the cells to agglutinate, thus obscuring the reading at low serum dilutions. This disadvantage can be overcome by the addition of sodium carbonate, which forms an insoluble compound with manganous chloride and does not interfere with antibody determination. The procedure presents a further refinement of the hemagglutination inhibition test for rubella by increasing specificity and sensitivity; it permits detection of antibody levels as low as 1:4 in sera.